Strategi Guru PAI Dalam Meningkatkan Kreativitas Siswa pada Pembelajaran di MTSN 3 Pasaman Barat - Anwar, Riza Rizkiah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This research is motivated by the fact that a teacher in carrying out teaching only carries out his obligations and duties as an educator, and does not have the skills and professionals in carrying out his duties as a teacher, to further enhance student creativity, so that goals are achieved, both National Education goals and school goals. The problem in this study is how the PAI teacher's strategy in increasing student creativity in learning at MTS N 3 Pasaman Barat and what are the inhibiting and supporting factors of the teacher's efforts in developing student creativity. There are two objectives in thisstudy, namely: (1) To produce methods, ways, ideas, and strategies to increase students' creativity in learning, so that the learning situation is more lively and enjoyable. (2). Increasing student effectiveness so that student achievement can be improved. The method used is the descriptive qualitative method. The results of this study explain that increasing student creativity in learning at MTS N 3 Pasaman Barat is carried out using lecture, discussion, question and answer, assignment, and demonstration methods. Themedia used are infocus and PowerPoint. While the models used by PAI teachers are jigsaw learning, the power of two, and practice. The school environment strongly supports the implementation of PAI teachers' creative learning by providing complete facilities and infrastructure. The skills possessed by students include reading the Qur'an well and holding other religious activities. This is evident from the results of observations on the level of student creativity that has increased after the strategies carried outby the PAI teacher, by using methods, media, and practicing several learning models so that the level of student creativity is much-increased learning.